Towards electro-thermo-mechanical simulation of integrated circuits in standard CAD environment. Issue 12 (December 2015) - Garci, Maroua; Kammerer, Jean-Baptiste; Hebrard, Luc
Abstract: Through mechanical coupling, thermal effects can lead to drifts in circuits׳ electrical performances, as well as integrated circuits reliability issues. It is thus necessary to consider thermal, mechanical and electrical effects all together in a self-consistent manner. This work focuses on the electro-thermo-mechanical simulation of integrated circuits, performed in a unique Computer Aided Design environment, in the target of ICs reliability monitoring from the early design stages. An electro-thermo-mechanical simulation tool was developed using the Cadence® environment and the Spectre® simulator. The simulation principle is based on the direct approach with a mixed compact and finite element modelling. Three networks, i.e. the electrical, the thermal and the mechanical networks are automatically generated, linked together, and then simulated using a single simulator, i.e. Spectre®. The electro-thermal modelling being already developed, this paper is focused on the finite element modelling of the thermo-mechanical effects using the behavioural language Verilog-A. First simulation results on a single silicon cube have been compared with results obtained from COMSOL Multiphysics®, showing a good agreement. Finally a simplified two-material integrated circuit featuring a power device has been simulated in order to show the possibilities of the tool.